(untitled) (UNIZIK Journal of Marketing, 2026)
In today’s competitive banking sector, where customer satisfaction is increasingly influenced by digital interactions, banks must adopt effective digital marketing strategies to enhance service delivery and retain clients. This study therefore examines the effect of digital marketing on customer satisfaction in selected deposit money banks in Awka Metropolis, Anambra State. The specific objectives were to: (i) ascertain the influence of mobile payment services on customer satisfaction; (ii) determine the effect of online banking experience on customer satisfaction; (iii) examine the impact of social media engagement on customer satisfaction; and (iv) identify the effect of mobile banking applications on customer satisfaction. The study adopted a descriptive survey design, with data collected through structured questionnaires administered to 180 respondents selected using simple random sampling. Data were analyzed using descriptive statistics and regression analysis. The findings revealed that mobile payment services significantly influence customer satisfaction (B = 0.286, p = 0.000), online banking experience has a positive effect (B = 0.085, p = 0.025), social media engagement significantly impacts satisfaction (B = 0.332, p = 0.007), and mobile banking applications positively affect customer satisfaction (B = 0.216, p = 0.000). The study concludes that digital marketing tools play a critical role in enhancing customer satisfaction in the banking sector. It recommends that banks invest in improving mobile payment platforms, enhance online banking interfaces, actively engage customers on social media, and continuously upgrade mobile banking applications to maintain high levels of customer satisfaction.